Study on Begollia of Sarawak : Population and Distribution of Begollia spp. in the Foothill of Limestone Areas in Kuching Division - Nabila, Binti Satibi (Universiti Malaysia Sarawak (UNIMAS), 2011)
Limestone is a sedimentary rock which can form by inorganically or biochemically process. This limestone is very unique habitat and occupies only small land area where many endemic plant species are found. Begoniaceae is one of the largest flowering plant families with an estimation about I, 600 species throughout the world. Main objective of the study is to gather information on population and distribution of Begonia species from the foothill of limestone and to compare the diversity and density of Begonia from three selected areas, Bau, Padawan and Serian. Five plots (20 x 20 m) with subplots 10 x to m were set up in each study sites. The data that have been recorded were calculated for mean and standard deviation. The highest mean is at Serian limestone areas which is 186.2. Standard deviation for three selected study areas in Bau, Padawan and Serian is 40.7, 247.2 and 202.2. Ten taxa were recorded during this study which were seven taxa recorded within the plots whereby three other taxa were recorded outside the plots.